The Development of a New Approach for the Harmonized Multi-Sectoral and Multi-Country Cost Valuation of Services: The PECUNIA Reference Unit Cost (RUC) Templates - Susanne Mayer; Michael Berger; Nataša Perić; Claudia Fischer; Alexander Konnopka; Valentin Brodszky; Silvia M. A. A. Evers; Leona Hakkaart-van Roijen; Mencia Ruiz Guitérrez Colosia; Luis Salvador-Carulla; A-La Park; Joanna Thorn; et al. (Applied Health Economics and Health Policy, 2024)
Background: Increasing healthcare costs require evidence-based resource use allocation for which assessing costs rigorously and comparably is crucial. Harmonized cross-country costing methods for evaluating interventions from a societal perspective are lacking. This study presents the development process and content of the service costing templates developed as part of the European project PECUNIA. Methods: The six developmental steps towards technological readiness of the templates included (1) a common conceptual costing framework and review of methodological costing issues, (2) harmonization strategy formulation, (3) proof-of-concept with expert feedback, (4) piloting, (5) validation, and (6) demonstration in six European countries. Results: The PECUNIA Reference Unit Cost (RUC) Templates for service costing are three new self-completion tools to be used with secondary or primary data for top-down micro-costing or top-down gross-costing approaches. Complementary data collection and unit cost aggregation/weighting templates are available. The applications leading to the final versions including (4) piloting through calculation of 15-unit costs, (5) validation within a Health Technology Assessment framework, and (6) RUC calculations mostly based on secondary data demonstrated the templates' general feasibility, with feedback for improved usability incorporated and a supplementary user guide developed. Conclusion: The validated PECUNIA RUC Templates for multi-sectoral and multi-country service costing allow for harmonized RUC development while incorporating flexibility and transparency in the choice of costing approaches, data sources and magnitude of remaining heterogeneity. The templates are expected to significantly improve the quality, comparability and availability of unit costs for economic evaluations, and promote the transferability of service cost information across Europe.
Keywords: 610